Manajemen Komunikasi Politik Jokowi dan Ma’ruf Amin Pada Pemilihan Presiden untuk Meningkatkan Dukungan Masyarakat - afifa, Ummu; Mahmud, Akmal Abdussalam; Ananda, Darra (Jurnal Ilmu Komunikasi, 2023)
This aims of research to analyze the political communication management carried out by the Joko Widodo and Ma’ruf Amin campaign teams in the 2019 presidential election. This research method uses a descriptive qualitative type and approach. The research results show that the Jokowi and Ma’ruf Amin campaign team used a communication strategy by utilizing conventional media and digital platforms to spread their message widely. This strategy includes careful media management, public relations focused on building a positive image, and the use of social media to interact with voters and mobilize support. Communication management also plays an important role in optimizing the president’s work program and equitable national development. Jokowi utilizes clear policy messages, direct engagement with the community, and collaborative partnerships to encourage equitable development and improve community welfare. Implementation of this strategy contributes to increasing public awareness, building trust and credibility, and mobilizing support from various levels of society